Linum usitatissimum as an antimicrobial agent and a potential natural healer: a review - Fadzir, Ummu Afifah; Darnis, Deny Susanti; Mustafa Al-Ahmad, Basma Ezzat; Mokhtar@Makhtar, Khairani Idah (Penerbit Universiti Sains Malaysia, 2018)
Linum usitatissimum commonly known as flaxseed is one of the oldest crops traditionally cultivated mainly for its oil purposes. Flaxseed is widely known for its rich source of nutritive and bioactive compounds. Recently, it has gained considerable interest due to the potential health benefits attributed to its component of metabolites, including its antimicrobial properties. Two main components of flaxseed, the unsaturated fatty acids and lignan, are suggested as the main metabolites that exhibit antimicrobial activities. This paper aims to give an overview on fatty acid and phenolic compound in flaxseed and their possible activities as antimicrobial agents.